PEMANFAATAN TANAH ULAYAT UNTUK PENDIRIAN TONDOK DI KABUPATEN MAMASA - Lisma Lumentut (Paulus Law Journal, 2021)
The establishment of Tondok is one of the process of utilization of land rights in Mamasa area, but the utilization of land rights is not regulated in a regional regulation of Mamasa Regency. This research aims to find out how the process of utilizing land rights ulayat for the establishment of Tondok in Mamasa area as well as how the status of land occupied by individuals in Tondok. This research uses Empirical Juridical with historical and case approaches. The results of this study show that in the process of utilizing land rights ulayat for the establishment of Tondok in Mamasa area was carried out on mutual consent by indigenous leaders and citizens of mamasa indigenous law community. The status of land individually in Tondok is recognized as a joint right and the rights of individuals are recognized in a limited way because it is considered a right of use and the prohibition of the recognition of land as property except in the form of rice fields.